PENGARUH SISTEM PENGENDALIAN INTERN PEMERINTAH, SISTEM APLIKASI KEUANGAN TINGKAT INSTANSI, DAN KOMPETENSI SUMBER DAYA MANUSIA TERHADAP KUALITAS LAPORAN KEUANGAN DENGAN GOOD GOVERNMENT GOVERNANCE SEBAGAI VARIABEL INTERVENING - Pangaribuan, Dessy Kristanti; Widyastuti, Tri; Zulkifli; Simanjuntak, Risma Adelina (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2024)
The aim of this research is to test and analyze the influence of the government's internal control system, agency level financial application system, human resource competency on the quality of financial reports with good government governance as an intervening variable. This research uses a quantitative approach with a questionnaire survey given to all financial managers at the Directorate General of Economic Development and Investment in Villages, Disadvantaged Regions and Transmigration. The questionnaire that could be processed was 68 respondents. Data analysis uses PLS structural equation modeling. This research shows that the government's internal control system, agency level financial application system and human resource competency influence good government governance. The government's internal control system, agency level financial application system and human resource competency influence the quality of financial reports and good government governance also influences the quality of financial reports. From the results of this research, human resource competency has the greatest influence on good government governance. Competent human resources are very necessary so that financial management can be accounted for in a timely, transparent and accountable manner. It is hoped that the implications of this research can provide evaluation material for policy makers to create policies to improve the quality of financial reports.